Outcome of central laminectomy and lateral mass screw fixation in multilevel cervical spondylotic myelopathy. our experience at Ghurki Trust Teaching Hospital, Lahore - Faraz Ahmad Khan; Farman-Ul-Haq; Latif Khan; Anwar Imran; Farhan Qazi; Rizwan Akram (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse clinical and radiological outcomes of central laminectomy and lateral mass screw fixation from C3 to C6 in multilevel cervical spondylotic myelopathy. Method: The retrospective cohort study was conducted at the Department of Orthopaedic and Spine Surgery, Ghurki Trust Teaching Hospital Lahore, Pakistan, from March 1 to August 31, 2023, and comprised data of patients who underwent central laminectomy and lateral mass screw fixation from C3 to C6 by magrel technique between March 2015 and August 2022, and were followed up till 1 year. Clinical outcomes were evaluated according to the Nurik grade and the modified Japanese Orthopedic Association scoring system. Radiological outcomes were assessed by Cobb’s method. Data was analysed using SPSS 27. Results: Of the 66 patients, 56(86.2%) were males and 9(13.8%) were females. The overall mean age at the time of surgery was 56.81±10.96 years (range: 45-75 years). Mean preoperative cervical lordosis was 10.5±3.70 and postoperative lordosis was 21.44±8.20. The mean preoperative and postoperative modified Japanese Orthopedic Association scores were 4.21±1.79 and 7.08±2.64, respectively. There were 32(49.2%) patients in Nurik grade 0, 2(3%) in grade 1, 10(15.4%) in grade 4, 12(18.5%) in grade 5 and 10(15.4%) in grade 6. There were 5(7.6%) cases of intraoperative iatrogenic dural tears, which were repaired with 7.0 prolene, and 7(10.6%) patients’ wound infections were treated with wound wash and intravenous antibiotics. Conclusion: Cental laminectomy and lateral mass screw fixation in multilevel degenerative spondylotic myelopathy were found to be safe and effective procedures with good to excellent results.